Ines Härtel (Editor), Handbook of Agri-Food Law in China, Germany, European Union. Food Security, Food Safety, Sustainable Use of Resources in Agriculture, Springer 2017, ss. 662. - Budzinowski, Roman; Goździewicz-Biechońska, Justyna (Przegląd Prawa Rolnego, 2018)
Recenzja